Self-regulation of the newlyweds in Taiwan: Goals and strategies. (August 2020) - Chang, Szu-Chia; Chang, Jenny Hsiu-Ying; Low, Meng-Yeow; Chen, Tzu-Chin; Kuo, Shih-Hsien
The aim of this study is to explore the goals and strategies of self-regulation of the newlyweds in Taiwan. Through in-depth interviews with eight newlywed couples ( N = 16), qualitative data were gathered and analyzed using thematic analysis. The findings revealed that, under the influence of their cultural values, the newlywed participants pursue the goals of genuine harmony and superficial harmony in their self-regulation for marital adjustment. Genuine harmony can be attained through people's fulfillment of their role norms in in-law relationships and establishment of affiliations with spouses in marital relationships. On the other hand, superficial harmony can be maintained by people through keeping sketchy relationships with their in-laws and inhibiting anger to prevent open conflicts with their spouses. To achieve relational harmony, various strategies of self-regulation were used depending on the situations involved. Such strategies direct to the principle of zhong-yong (the Doctrine of Mean) involving holistic information processing and avoidance of extremities in implementation. Gender differences in self-regulation were found in both goals and strategies.